Spatial Distribution of Elemental Enrichments around Archaeological Sites: Insights from the Ancient City of Sagalassos in Southwest Turkey. Issue 1 (25th November 2015) - Dirix, K.; Muchez, P.; Degryse, P.; Poblome, J.
Abstract : Ancient human activities have resulted in important elemental enrichments in soils at archaeological sites. Nevertheless, the spatial extent of such elemental enrichment signals is rarely studied. Our research addresses this theme by studying the characteristics and extent of the geochemical enrichment halo around the monumental Colonnaded Street of the Hellenistic to Byzantine city of Sagalassos in southwest Turkey. Given the complex geology of the area, a strategy applying multivariate statistical data analysis techniques is proposed to identify whether the enrichments have a geological or an anthropogenic source. In addition, we evaluate how a wide variety of natural and anthropogenic processes may influence the distribution of elements around the site. In this paper, it is shown that enrichments of P and Pb are present up to a distance of 450 m and 150 m away from the city, respectively. Hence, we conclude that the extent of chemical enrichment haloes around archaeological sites may be element specific.